Realizing Efficient Lead‐Free Formamidinium Tin Triiodide Perovskite Solar Cells via a Sequential Deposition Route - Zhu, Zonglong; Chueh, Chu‐Chen; Li, Nan; Mao, Chengyi; Jen, Alex K.‐Y. (Advanced materials (Weinheim), 2018)
Recently, the evolved intermediate phase based on iodoplumbate anions that mediates perovskite crystallization has been embodied as the Lewis acid–base adduct formed by metal halides (serve as Lewis acid) and polar aprotic solvents (serve as Lewis base). Based on this principle, it is proposed to constitute efficient Lewis acid–base adduct in the SnI2 deposition step to modulate its volume expansion and fast reaction with methylammonium iodide (MAI)/formamidinium iodide (FAI) (FAI is studied hereafter). Herein, trimethylamine (TMA) is employed as the additional Lewis base in the tin halide solution to form SnY2–TMA complexes (Y = I−, F−) in the first‐step deposition, followed by intercalating with FAI to convert into FASnI. It is shown that TMA can facilitate homogeneous film formation of a SnI2 (+SnF2) layer by effectively forming intermediate SnY2–TMA complexes. Meanwhile, its relatively larger size and weaker affinity with SnI2 than FA+ ions will facilitate the intramolecular exchange with FA+ ions, thereby enabling the formation of dense and compact FASnI3 film with large crystalline domain (>1 µm). As a result, high power conversion efficiencies of 4.34% and 7.09% with decent stability are successfully accomplished in both conventional and inverted perovskite solar cells, respectively. High‐performance FASnI3 perovskite solar cells (PVSCs) are realized for the first time by a two‐step deposition technique. Trimethylamine (TMA) is used as an additive to improve the morphology, enabling a dense and compact FASnI3 film with large crystalline domains (>1 μm). Consequently, high PCEs of 4.34% and 7.09% can be successfully realized in both conventional and inverted PVSCs with improved stability.